Joseph R. Levenson, Modern China and its Confucian past, Doubleday, New York, 1964. 246 pp. - Botton Beja, Flora (Estudios de Asia y África, 1966)
Joseph R. Levenson, Modern China and its Confucian past, Doubleday, New York, 1964. 246 pp.